Forming speech at the preschooler with special needs through the prism of humanistic paradigm of education (Pedagogy of Higher and Secondary Education, 2013)
Ashуtok N. I. Forming speech at the preschooler with special needs through the prism of humanistic paradigm of education.The article deals with the problem of studying the state of organizing creative coherent speech at the preschooler with delay of mental development and determination of effective methods and tools which provide for forming and development communicative knowledge of definite category of children.
Keywords: child with the delay of method development; language activity; creative coherent speech; abstract thoughts; imagination; school establishments